Evaluation of three different agents for in-office treatment of dentinal hypersensitivity: A controlled clinical study - Shruti A Patil; Balaram D Naik; R Suma (Wolters Kluwer Medknow Publications, 2015)
Context: Dentin desensitizers are used for in-office treatment of dentinal hypersensitivity. They block the open tubules and bring about a reduction in hypersensitivity. Aim: The aim was to evaluate and compare the clinical effectiveness of a dentin desensitizer, a combination of a dentin desensitizer + adhesive and one-bottle self-etching adhesive for in-office treatment of dentin hypersensitivity. Settings and Design: Institutional, prospective double-blind parallel clinical design. Subjects and Methods: A total of 54 teeth in 20 patients were randomly allocated to one of the three study groups, with 18 teeth in each group as follows: Group A-Gluma Desensitizer (GD), Group B-Gluma Comfort Bond + Desensitizer (GCBD), Group C-Single Bond Universal (SBU). The patients' dentinal hypersensitivity scores for tactile (hand-held scratch device), thermal (cold), and evaporative (dental unit air syringe) stimuli were recorded on a visual analog scale. The parameters were recorded at baseline, immediately after application of the agent, 3- and 6-week posttreatment. Statistical Analysis Used: The data were analyzed with Friedman's test, Wilcoxon signed ranks test, Kruskal-Wallis test, and Mann-Whitney-U-test (P < 0.05). Results: All three groups showed a significant reduction in dentinal hypersensitivity (P < 0.05) compared to baseline at all time intervals. Statistically, significant differences were noted between GD and SBU; between GCBD and SBU in all testing parameters. Between GD and GCBD no significant difference was noted. Conclusions: GD and GCBD showed a greater reduction in dentin hypersensitivity than SBU